Hedging Strategy to Mitigate Exchange Rate Risk in Cross-Border Transactions: Literature Review - Zai, Faniswan Seprilian; Mansur, Ahmad (Journal of Business Management and Economic Development, 2024)
This literature review examines hedging strategies employed by companies to mitigate foreign exchange risk in cross-border transactions. The aim is to synthesize findings from existing studies to provide a comprehensive understanding of the effectiveness, determinants, and challenges of currency hedging practices. The review follows a systematic approach, including searching, selecting, and analyzing relevant literature from 2018 to 2024. The findings reveal that companies actively use various derivative instruments and operational hedging techniques to manage exchange rate exposure. While many studies demonstrate the effectiveness of hedging strategies in reducing risk and enhancing firm performance, some report inconsistent results, suggesting that hedging effectiveness can vary depending on various factors. Firm size, financial leverage, growth opportunities, and the level of exchange rate exposure consistently influence firms' decisions to hedge. However, implementing hedging strategies also faces challenges related to instrument selection, transaction costs, margin requirements, and accounting treatment. The review identifies research gaps, including the need for studies in emerging markets, exploration of innovative hedging techniques, integrated research approaches, and investigation of the non-financial impacts of hedging. The findings contribute to our understanding of currency hedging strategies and provide valuable insights for companies in managing exchange rate risk in an increasingly dynamic global business environment.